Are there long-term benefits of experiential, interprofessional education for non-specialists on clinical behaviours and outcomes in diabetes care? A cohort study. Issue 1 (8th January 2016) - Ching, Daniel; Forte, Denise; Aitchison, Elizabeth; Earle, Kenneth
Abstract : Objectives: Our aim was to assess the impact of an educational initiative for non-specialist, healthcare professionals in the community on the process and quality measures of diabetes care delivered, and changes in their learning experiences and clinical management behaviour in the short and long term. Setting: Single locality of 26 primary care practices associated with one secondary centre. Participants: General practitioners and practice nurses managing 4167 patients with diabetes. Intervention: A rolling 10-week, experiential, interprofessional education programme delivered to 57 practitioners and observations in practice. Primary and secondary outcome measures: Primary outcomes were changes in the proportion of patients receiving foot care, urine albumin:creatinine ratio assessments and achieving National Quality Outcome Framework targets for blood pressure (<145/80 mm Hg), glycated haemoglobin (HbA1c; >86 mmol/mol (10%) and <57.4 mmol/mol (7.4%)) and total cholesterol (<5 mmol/L) thresholds. Secondary outcomes were evidence of sustained learning and changes in the number of patients referred to secondary care. Results: Evaluation of care processes and quality outcomes took place 15 months after the programme was initiated. The proportion of patients with a HbA1c of <57.4 mmol/mol (7.4%) and >85 mmol/mol (10%) was significantly higher (44% vs 53% p=0.0001) and lower (12.5% vs 10%; p=0.002) respectively. There was an increase in the proportion (95% CI) of patients receiving foot care reviews (+26.0% (24.0% to 28.1%)), microalbuminuria screening (+29.8% (27.7% to 31.9%)) and who achieved targets for blood pressure (+9.6% (7.5% to 11.6%)) and total cholesterol (+14.4% (12.3% to 16.5%); p<0.001). 241 fewer patients were referred to secondary care. Increases in the healthcare professional's confidence and collaborative clinical behaviour were evident 3 years after completing the programme. Conclusions: An experiential, interprofessional intervention can result in significant improvements in quality outcomes in association with a sustained impact on behaviours and practices.